2016
DOI: 10.1210/jc.2015-2724
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Induces Postmenopausal Dyslipidemia Through Inhibiting Hepatic Cholesterol Metabolism

Abstract: FSH may interact with its receptors in hepatocytes and reduce LDLR levels, which subsequently attenuates the endocytosis of LDL-C, resulting in an elevated circulating LDL-C level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 35 publications
7
123
2
Order By: Relevance
“…Further supporting the therapeutic potential of FSHRCER T-cells, we confirmed that only tumor-free ovaries, and not any other healthy human tissues tested, expressed FSHR at the mRNA level ( Figure 3a ). Of note, this includes liver tissue, where a recent report has suggested possible expression of FSHR in tissue surrounding a hepatocellular carcinoma (35). …”
Section: Resultsmentioning
confidence: 99%
“…Further supporting the therapeutic potential of FSHRCER T-cells, we confirmed that only tumor-free ovaries, and not any other healthy human tissues tested, expressed FSHR at the mRNA level ( Figure 3a ). Of note, this includes liver tissue, where a recent report has suggested possible expression of FSHR in tissue surrounding a hepatocellular carcinoma (35). …”
Section: Resultsmentioning
confidence: 99%
“…Postmenopausal status is characterized by high levels of FSH and LH, as well as low levels of E2, making it difficult to explore the precise role of FSH in renal function in the OVX mouse model. To diminish the potential effect of these two parameters, we used GnRHa‐treated ovariectomized mice administered with recombinant FSH in accordance with several studies (Li, Chen, et al, ; Song et al, ). Given that kidney injury is a relatively chronic process, we increased the dose of FSH from 0.15 IU to 0.3 IU and lengthened intervention time to 6 weeks, which was different from Liu's study on fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial elevation in the serum follicle‐stimulating hormone level, although likely to compensate for estrogen withdrawal, has been closely involved in the adverse effects of menopause on many nongonadal tissues, including bone (Sponton & Kajimura, ), liver (Song et al, ), adipose tissue (Liu et al, ), umbilical vascular endothelial cell (Siraj et al, ), and biliary epithelium (Onori et al, ). Functional follicle‐stimulating hormone receptors (FSHRs) were also reported to exist in these extragonadal tissues to regulate bone, glucose, and lipid metabolism (Qi et al, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that FSHR can exist in extragonadal tissues, including the various locations of the female reproductive tract [16,31], the developing placenta [32], tumor vasculature and metastases [33] and other locations [34,35]. mRNA and protein of FSHR wild type or its variants are also expressed in bovine granulosa cells [36] and in the blood vessels of human malignant tumors [22].…”
Section: Fshr Expression In Extragonadal Tissuesmentioning
confidence: 99%
“…An earlier study found the placental growth defects and fetal loss were associated with FSHR expression in mice [32]. Additionally, FSHR may be involved in expressing the low-density lipoprotein receptor and regulating low-density lipoprotein cholesterol clearance in liver tissues [35]. Currently, it remains unclear whether these FSHR are structurally similar to those primarily expressed in the gonad tissues, and it is vital that the physiological functions of FSHR extragonadal expressions are clearly identified.…”
Section: Fshr Expression In Extragonadal Tissuesmentioning
confidence: 99%